Taping for plantar fasciitis on the ATP tennis circuit - Novotny, M. (Medicine and Science in Tennis, 2004)
About taping as an important adjunct in the treatment regimen for plantar fasciitis in the tennis athlete. When properly applied, taping can reduce the stretching of the plantar fascia, resulting in significant pain relief.